Impacts of the SARS-CoV-2 pandemic on the dietary practices of university students in Germany - Dreyer, Jana O.; Brandt, Alexander C.; Lichtenstein, Silke; Sina, Christian; Smollich, Martin (Frontiers in Nutrition, 2024)
Purpose: The dietary practices (DPs) of university students are influenced by many external factors. Therefore, we investigate how the DPs of students in Germany changed during the SARS-CoV-2 pandemic, what the main motivations were for those changes, and what effect the closure of university catering had on the DPs of students.Methods: A total of 560 students from two universities in Lübeck (Germany) were surveyed online during a pilot phase. The final online questionnaire was subsequently administered at 10 other German universities (399 respondents). The questionnaire surveyed sociodemographic factors, dietary habits, food consumption frequencies, and the relevance of university catering before and during the SARS-CoV-2 pandemic.Results: Regarding changes in DPs, similarities to previous studies were found, especially positive eating behaviors and an increasing interest in health-and nutritionrelated sustainability. Students prepared meals freshly more often during the pandemic; consumed legumes, plant-based meats and dairy alternatives more often; and reduced their consumption of meat and milk compared to before the pandemic.The consumption frequency of sweets also decreased. It was observed that students consider eating communal in the university canteen to be highly relevant for their social interactions, which was only possible to a limited extent during the pandemicA high relevance of commensality for university catering was observed.In Germany, the DPs of university students as well as criteria regarding health and sustainability changed during the first two years of the SARS-CoV-2 pandemic. The social aspect of DPs became evident due to closed university catering.Still, changes in dietary patterns and eating habits were positively related to health and revealed some differences in the cross section of the population.